Optimizing Block System Management in the P5-PPRA Project Based Learning in Elementary School and Madrasah Ibtidaiyah - Nurlaeli, Nurlaeli; Krisetyaningsih, Krisetyaningsih; Faisal, Faisal; Aquami, Aquami; Wasilah, Wasilah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
The implementation of the Pancasila Student Profile Strengthening Project (P5) continues to face various challenges, particularly in faith-based primary education institutions. This study offers a novel perspective by examining the management of the P5-PPRA program through a block system in elementary schools and Madrasah Ibtidaiyah. This area remains underexplored in empirical research. The study aims to analyze management strategies, the roles of educational stakeholders, and the supporting and inhibiting factors in the implementation of the block-system-based P5-PPRA program. A qualitative multi-case study Design was employed involving two primary education institutions in Palembang City. Data were collected through in-depth interviews with school principals and teachers, as well as structured observations of P5-PPRA implementation, and analyzed using thematic analysis. The findings indicate that the optimization of the P5-PPRA program is influenced by integrated program planning, adaptive school leadership, teacher competence in project-based learning, and flexible time management through the block system. However, limitations in teachers’ conceptual understanding, resource readiness, and insufficient policy support remain significant challenges. This study contributes to the existing literature by proposing a conceptual management model for implementing the P5-PPRA program through a block system, which can serve as a reference for policymakers and education practitioners in enhancing the effectiveness of character education in primary schools.